Penatalaksanaan Fisioterapi Pada Kasus Paraparese di RSUD Karangayar - Bakti, Muhammad Ridha, Agus Widodo SST.FT, M.Fis (2015)
Paraparese is the loss of motor function of the two limbs. Paraparese cause by a great compression so that it can destroy the corpus vertebrae that causes failure of the vertebral column in the anterior and middle in defending its position.To know the benefits of granting Infra Red, TENS, and Exercise Therapy in simulating improvement sensibility, increasing muscle strength and ability of the functional activities.Provision of Infra Red, TENS and Exercise Therapy may improve muscle strength.